(untitled) (Journal of Social Sciences Review, 2023)
The value of digital evidence has expanded quickly in recent years due to increases in its dependability and complexity. Evident from national and international regulations. There is a presumption in the law that digital evidence is admissible, and authorities have been directed not to rule it out of court because it is not presented in a substantive and perceptible form. Domestic and international laws have educated domestic law, and today everyone agrees. This section examines the background of the issue, the laws at play, and how it presented the matter to the Supreme Court nationwide. The technique adopted in this review study is a literature search. "Digital evidence" refers to any evidence made, kept, or transferred via digital means. It is impossible to overstate the role that digital evidence plays in the administration of criminal justice. In Pakistan, there were no laws surrounding the acceptance of digital evidence in court until 2002. We review roughly twenty evaluations given by different scholars in their articles. Part one of this review article’s subsections is split in two. These abstracts expand upon the newest parts of the supplied legislation. The last section often supplies a quick summary of the important points and supporting evidence presented throughout the essay.